Liver Metastasis or Granulomatous Hepatitis: A Diagnostic Dilemma - Sinha, Sachin; Sharma, Charu; Garg, Pallavi; Singla, Vikas; Bhargava, Richa; Madan, Kaushal (Journal of Gastrointestinal Infections, 2025)
Granulomatous liver involvement, which may occur in a variety of infective, inflammatory, and malignant cases, is a rare condition. We present an interesting case of prostate carcinoma presenting as a localized, ill-defined FDG-avid liver lesion, which turned out to be nonmalignant granulomatous hepatitis. Correct histological diagnosis changed a probable dismal prognosis to a completely curable cause.
Keywords: FDG-avid liver lesion; granulomatous hepatitis; hepatic tuberculosis